Making climate policy work - Cullenward, Danny; Victor, David G. (Polity Press, 2020)
For decades, the world's governments have struggled to move from talk to action on climate. Many now hope that growing public concern will lead to greater policy ambition, but the most widely promoted strategy to address the climate crisis--the use of market-based programs--hasn't been working and isn't ready to scale. Danny Cullenward and David Victor show how the politics of creating and maintaining market-based policies render them ineffective nearly everywhere they have been applied. Reforms can help around the margins, but markets' problems are structural and won't disappear with increasing demand for climate solutions. Facing that reality requires relying more heavily on smart regulations and industrial policy--government-led strategies--to catalyze the transformation that markets promise, but rarely deliver. --Back cover.